A decrease in the addition of new cells in the nucleus accumbens and prefrontal cortex between puberty and adulthood in male rats. Issue 6 (20th January 2014) - Staffend, Nancy A.; Mohr, Margaret A.; DonCarlos, Lydia L.; Sisk, Cheryl L.
ABSTRACT Adolescence involves shifts in social behaviors, behavioral flexibility, and adaptive risk‐taking that coincide with structural remodeling of the brain. We previously showed that new cells are added to brain regions associated with sexual behaviors, suggesting that cytogenesis may be a mechanism for acquiring adult‐typical behaviors during adolescence. Whether pubertal cell addition occurs in brain regions associated with behavioral flexibility or motivation and whether these patterns differ between pubertal and adult animals had not been determined. Therefore, we assessed patterns of cell proliferation or survival in the prefrontal cortex and nucleus accumbens. Pubertal and adult male rats were given injections of bromo‐deoxyuridine (BrdU). To assess cell proliferation, half of the animals from each group were sacrificed 24 h following the last injection. The remaining animals were sacrificed at Day 30 following the last injection to evaluate cell survival. Adult animals had significantly lower densities of BrdU‐immunoreactive (ir) cells in the prefrontal cortex, irrespective of post‐BrdU survival time, whereas in the nucleus accumbens, adult animals had a lower density of BrdU‐ir cells at the short survival time; however, the density of BrdU‐ir cells was equivalent in pubertal and adult animals at the longer survival time. These data provide evidence that cell addition during puberty may contribute to the remodeling of brain regions associated with behavioral flexibility and motivation, and this cell addition continues into adulthood, albeit at lower levels. Higher levels of cell proliferation or survival in younger animals may reflect a higher level of plasticity, possibly contributing to the dynamic remodeling of the pubertal brain. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 633–642, 2014